2016
DOI: 10.1016/j.rbre.2015.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome in patients with rheumatoid arthritis followed at a University Hospital in Northeastern Brazil

Abstract: RA patients in a tertiary center in Northeastern Brazil showed high prevalence of MS. It is worth noting that almost all patients had MS and abdominal obesity, which has important practical implications. In addition to the components of MS, age and smoking were associated with this syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 39 publications
0
8
0
1
Order By: Relevance
“…[28] F o r P e e r R e v i e w 14 Chronic steroid use in patients with diverse autoimmune diseases has been associated with an increased risk of metabolic syndrome and cardiovascular disease due to its enhancement of plaque formation, arterial stiffness, insulin resistance and lipid levels. [29][30][31] Perversely, the suppression of inflammation by steroids may also decrease the risk of cardiovascular disease, although there is limited outcomes data to demonstrate this. No study has previously compared outcomes between patients with RA depending on their steroid use.…”
Section: Discussionmentioning
confidence: 99%
“…[28] F o r P e e r R e v i e w 14 Chronic steroid use in patients with diverse autoimmune diseases has been associated with an increased risk of metabolic syndrome and cardiovascular disease due to its enhancement of plaque formation, arterial stiffness, insulin resistance and lipid levels. [29][30][31] Perversely, the suppression of inflammation by steroids may also decrease the risk of cardiovascular disease, although there is limited outcomes data to demonstrate this. No study has previously compared outcomes between patients with RA depending on their steroid use.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence regarding the impact of MetS on RA is mixed. Several studies that assessed patients with RA with MetS showed this population is more likely to have higher Health Assessment Questionnaire (HAQ) scores than patients without MetS; however, other studies have not shown a significant difference 37‐41 . Two large‐scale studies that included 100 patients showed that MetS was associated with high systemic inflammatory markers, disease activity, and disability scores compared with patients with RA but without MetS 42,43 .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, AS patients with a higher disease activity score also had a higher prevalence of MetS, so, it can be considered that MetS is closely related to a chronic inflammatory state which can affect the disease activity in AS patients. 20 showed that age was an independent predictor of MetS in patients with RA. Obesity is known to have a major role in the development of MetS.…”
Section: Discussionmentioning
confidence: 99%